Asia Pacific Business Process Management Second Asia Pacific Conference, AP-BPM 2014, Brisbane, QLD, Australia, July 3-4, 2014, Proceedings - Ouyang, Chun; Jung, Jae-Yoon (Lecture Notes in Business Information Processing, 2014)
This book constitutes the proceedings of the Second Asia Pacific Conference on Business Process Management held in Brisbane, QLD, Australia, in July 2014. In all, 33 contributions from 12 countries were submitted. After each submission was reviewed by at least three Program Committee members, nine full papers were accepted for publication in this volume. These nine papers cover various topics that can be categorized under four main research focuses in BPM: process mining, process modeling and repositories, process model comparison, and process analysis.